Penerapan Micro Teaching Dalam Meningkatkan Kompetensi Pedagogik Calon Guru PAI - Afifah Zahra Manday; Safitri, Noviyanda; Ramadani Fitri Ginting (CV. Ulil Albab Corp, 2025)
Abstract: This study aims to describe the implementation of micro teaching in improving the pedagogical competence of prospective Islamic Education (PAI) teachers. Pedagogical competence is an essential aspect that teachers must possess, which includes the ability to plan, implement, and evaluate the learning process effectively. The research method used was a descriptive qualitative approach with the research subjects being prospective PAI teacher students in the micro teaching course. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that the application of micro teaching provides direct experience for students in classroom management, the use of varied teaching methods, and the improvement of pedagogical communication skills. Moreover, micro teaching helps prospective teachers to overcome nervousness, build self-confidence, and enhance professionalism as educators. Therefore, micro teaching has proven effective in developing the pedagogical competence of prospective PAI teachers and should continue to be optimized in teacher education programs.